UNIFORMITY DEGREE OF SOME SPHERICAL GRIDS USED IN MAGNETIC RESONANCE POWDER SIMULATIONS - CRĂCIUN, Cora (Studia Universitatis Babeș-Bolyai Physica, 2015)
This paper compares the uniformity degree of nine spherical grids used in magnetic resonance powder simulations. The comparison is based on known mesh quality measures, which depend on the grid points and the generated Voronoi regions on the unit sphere. According to computations, the distributions of the grids' geometric properties characterise better the grids' quality then the global uniformity metrics.